(untitled) (London, 1997)
The book provides knowledge on lamp technology and applications. This book describes the fundamentals of light, vision colour and measurement. The second part of the book deals with lamps and control equipment and includes description of all lamps types in use today. The book also covers interior and exterior applications of lighting
Keywords: Electric lighting,Electric lamps